2020
DOI: 10.1002/adts.202000185
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod Assisted Enhanced Plasmonic Detection Scheme of COVID‐19 SARS‐CoV‐2 Spike Protein

Abstract: The beautiful interplay between light and matter can give rise to many striking physical phenomena, surface plasmon resonance (SPR) being one of them. Plasmonic immunosensors monitor refractive index changes that occur as a result of specific ligand–analyte or antibody–antigen interactions taking place on the sensor surface. The coronavirus disease (COVID‐19) pandemic has jeopardized the entire world and has resulted in economic slowdown of most countries. In this work, a model of a sandwich plasmonic biosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 64 publications
0
58
0
Order By: Relevance
“…In the beginning, the proposed hybrid sensor performance was analyzed at different excitation wavelengths. Commercially available SPR biosensors such as Biacore-3000, SPRm-200, and Spreeta-2000 operate at a wavelength of 690 nm, 780 nm, and 830 nm, respectively [ 64 , 65 ]. The RI of sensor materials changes during the different excitation wavelengths, which is tabulated in Table 1 [ 34 ].…”
Section: Quality Enhancement Of the Proposed Sensormentioning
confidence: 99%
“…In the beginning, the proposed hybrid sensor performance was analyzed at different excitation wavelengths. Commercially available SPR biosensors such as Biacore-3000, SPRm-200, and Spreeta-2000 operate at a wavelength of 690 nm, 780 nm, and 830 nm, respectively [ 64 , 65 ]. The RI of sensor materials changes during the different excitation wavelengths, which is tabulated in Table 1 [ 34 ].…”
Section: Quality Enhancement Of the Proposed Sensormentioning
confidence: 99%
“…Das and his colleagues designed and simulated a plasmonic immunoassay, in 2020, which comprised of sandwich plasmonic biosensor whose sensitivity was enhanced by using gold nanorods. They have varied the prismatic configuration and found that the BK-7 glass-based sensor has a sensitivity of 111.11 deg./RIU [ 21 ]. They also varied the distance of the gold NRs and their aspect ratio and recorded their observations.…”
Section: Sensing Using Plasmonic Biosensorsmentioning
confidence: 99%
“…They claimed that their sensor had a limit of detection of around 4.2 fmol and sample-to-result duration was around 80 min [ 3 ]. In the same year, Das et al designed a gold nanorod-based plasmonic sensor to detect COVID-19 with a sensitivity of 111.11 deg./ RIU [ 21 ]. In 2018, Ahmed et al devised a sensor using magneto-plasmonic nanoparticles for coronavirus detection.…”
Section: Plasmonic Biosensors For Coronavirus Detectionmentioning
confidence: 99%
“…Then, samples containing the antigen were allowed to flow as an analyte. This work was assisted by a simulation technique to study the effect of ARs and arrangements of the gold nanorods [ 29 ].…”
Section: Novel Biosensing Strategies Used For Covid-19 Diagnosismentioning
confidence: 99%